Determination of forage yield and its components in blue melilot (Melilotus caerulea (L.) Desr.) grown in the western region of Turkey - Ates, Ertan (Cuban Journal of Agricultural Science, 2011)
The aim of this research was to determine the forage yield and its components in blue melilot (Melilotus caerulea (L.) Desr.) grown? in the western region of Turkey. Blue melilot seeds were collected during two years (2005-2006) at mature stage from grasslands (43.0 ?N, 26 ?E) of the Belovets village in Razgrad, the north-east of Bulgaria. This study was conducted during the 2006-2009 growing season (October-July) on xeralf soil with pH 6.8-7.1 at Field Crops Department experimental area (41.0 ?N, 27.5 ?E) in Agricultural Faculty of Namik Kemal University (Tekirdag), Turkey. The experimental design was a randomized complete block with four replicates. The plant height (cm), main stem diameter (mm), number of leaves per main stem, leaf length (cm), leaflet length (cm) and width (cm), green fodder yield (t ha-1), dry matter yield (t ha-1), crude protein (%) and fiber (%) were determined at the three growing stages such as ? bloom, ? bloom and full-bloom. It is concluded that green fodder yield (9.79-9.97 t ha-1) and dry matter yield (2.49-2.62 t ha-1) in the ? bloom and full-bloom stages were determined to be higher than in the rest of the stage. Quality is high if the crop is cut in the ? bloom stage. According to yield and other components, the blue melilot can be sown and cutting at ? bloom, ? bloom and full-bloom stages in the western of Turkey as well as in subtropical conditions. Key words: blue melilot, dry matter, green fodder, growth stage, Melilotus caerulea (L.) Desr.